Tandem copper-catalysed aryl and alkenyl amination reactions: the synthesis of N-functionalised indoles. - Hodgkinson, R; Schulz, J; Willis, M (2009)
A Cu-diamine complex effectively catalyses tandem C-N bond formation on 2-(2-haloalkenyl)-aryl halide substrates, to deliver a series of N-functionalised indoles. Anilines, amides and carbamates are all effective coupling partners under the developed conditions.